Akselerasi Pelatihan Perpajakan SMA Dian Bangsa Dalam Mengadapi Dunia Usaha Dunia kerja - Kurniawan; Antonius Juniarto (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
Tax revenue comes from several sources, one of which is taxation on individuals and business entities. Where Dian Bangsa High School sees that there are opportunities or opportunities that can be taken by graduates from that school. Because of that, Dian Bangsa High School conducted an assessment with Matana University to work together in improving or broadening the horizons of Dian Bangsa High School students in the field of taxation, especially article 21 income tax tax procedures. Therefore, the accounting study program carried out community service to Dian Bangsa High School based on the needs of the community. the school and will be carried out periodically and continuously. Based on data from the ministry of education and culture, the secretariat of the data center and statistics for education in 2022. There are 39 public vocational schools and 303 private vocational schools and 186 public high schools and 532 private high schools. so that graduates in the province of Banten. In the early stages of implementation, a mapping of SMA-SMK in the Banten Province will be carried out. Mapping will be done based on the distance traveled from Matana University to the school and the type of school (related to culture). Material 1 Motivate students to have an understanding of taxation, procedures for withholding and making individual tax returns. Contains about how to motivate students / wi in the spirit of learning to be able to face the challenges of technology that has entered industry 4.0 and information in the industrial world which asks a lot or requires students / wi to be able to compete and use technology well and quickly to encourage current industrial operational activities they enter the world of work. Thus, students can have an initial foundation in personal development as well as soft skills to find out which personal taxes they will apply in their work or education when dealing directly with the taxation sector. Material 2 contains an explanation of the making of an individual tax return in the world of work, also explains the calculation along with the tax rate. Thus, students have knowledge of letters as their basis for knowing tax letters, both personal and corporate, so that students have provisions related to tax letters that are often encountered. Material 3 contains case exercises about filling out personal notification letters, so that they understand how cases that occur in the field are not only in theory. Tax cases as well as a lot of learning make students honed their abilities and reasoning as well as training in solving cases that make them more skilled and have competent and expert competencies. Material 4 contains an evaluation of the training process for making personal notification letters and also case examples using a questionnaire given to students. Community service activities at Dian Bangsa High School are going well and according to procedures and have an impact on every student, seen from the final results in filling out the Individual Taxpayer Notification Letter.